أحكام قسمة المال الشائع في القانون المدني الجزائري - سمير غماري; منصور سلاطنية (My University, 2026)
Summary The division of jointly owned property is a crucial topic in Algerian civil law, as it is the legal means by which the state of joint ownership among partners is terminated, granting each partner a separate and independent share. Jointly owned property refers to property owned by two or more persons in common, without any one of them having a specific physical share. Rather, each partner owns an intangible share in it. The Algerian legislator has regulated the provisions for the division of jointly owned property within the texts of the Civil Code. It has established the principle of a partner's freedom to request division whenever they wish, considering joint ownership a temporary state in which no one is obligated to remain unless there is an agreement or legal provision stipulating otherwise. Division is divided into two types: consensual division, which takes place by agreement of all partners, and judicial division, which is carried out by the courts when agreement is not possible. The division is subject to a number of conditions and provisions, the most important of which are the legal capacity of the partners, the divisibility of the property without causing significant harm, and consideration of the nature of the jointly owned property, whether it is real estate or movable property. Partition may also be subject to certain impediments, such as a temporary agreement to remain in joint ownership or the attachment of third-party rights to the jointly owned property. Partition has significant legal consequences, most notably the termination of joint ownership and the transformation of a partner's share from a shared portion to a separate, distinct ownership. Partners are then responsible for protecting each other from claims and disputes as defined by law. Partition is considered declaratory of rights, not constitutive of them. This means that a partner is considered the owner of their share from the inception of joint ownership, not from the date of partition. The importance of studying the provisions governing the partition of jointly owned property lies in highlighting its role in achieving legal stability and protecting the rights of partners, as well as its contribution to reducing disputes that may arise from the continuation of joint ownership. ..................................... ملخص . تعدّ قسمة المال الشائع من المواضيع المهمة في القانون المدني الجزائري، باعتبارها الوسيلة القانونية التي تنهي حالة الشيوع بين الشركاء وتمنح لكل شريك نصيبًا مفرزا ومستقلًا عن باقي الأنصبة، ويقصد بالمال الشائع ذلك المال الذي يملكه شخصان أو أكثر على الشيوع دون أن يختص أيّ منهم بجزء مادي معين منه، وانما يملك كل شريك حصة معنوية فيه. وقد نظم المشرع الجزائري أحكام قسمة المال الشائع ضمن نصوص القانون المدني، حيث أقرّ مبدأ حرية الشريك في طلب القسمة متى شاء، باعتبار أن الشيوع حالة مؤقتة لا يجبر أحد على البقاء فيها، إلا إذا وجد اتفاق أو نص قانوني يقضي بخلاف ذلك. وتنقسم القسمة إلى قسمة رضائية تتم باتفاق جميع الشركاء، وقسمة قضائية تتم عن طريق القضاء عند تعذر الاتفاق. وتخضع القسمة لجملة من الشروط والأحكام، من أهمها أهلية الشركاء، وقابلية المال للقسمة دون إحداث ضرر جسيم، مع مراعاة طبيعة المال المشاع سواء كان عقارا أو منقولًا. كما قد ترد على القسمة بعض الموانع، مثل وجود اتفاق مؤقت على البقاء في الشيوع أو تعلق حقوق الغير بالمال المشاع. ويترتب عن القسمة آثار قانونية مهمة، أبرزها انتهاء حالة الشيوع وتحول حق الشريك من حصة شائعة إلى ملكية مفرزة، مع ضمان الشركاء لبعضهم البعض من التعرض والاستحقاق وفقا لما يحدده القانون. كما تعتبر القسمة كاشفة للحق وليست منشئة له، أي أن الشريك يعد مالكا لحصته منذ نشوء الشيوع لا من تاريخ القسمة. وتبرز أهمية دراسة أحكام قسمة المال الشائع في إبراز دورها في تحقيق الاستقرار القانوني وحماية حقوق الشركاء، إضافة إلى مساهمتها في الحد من النزاعات التي قد تنشأ بسبب استمرار حالة الشيوع. .................................... Résumé Le partage des biens indivis est une question cruciale en droit civil algérien, car il constitue le moyen légal de mettre fin à l'état de propriété conjointe entre associés, en conférant à chacun une part distincte et indépendante. Un bien indivis désigne un bien détenu en commun par deux personnes ou plus, sans qu'aucune d'entre elles ne possède de part matérielle spécifique. Chaque associé détient plutôt une part incorporelle du bien. Le législateur algérien a réglementé les dispositions relatives au partage des biens indivis dans le Code civil. Il a établi le principe de la liberté de chaque associé de demander le partage à tout moment, considérant la propriété conjointe comme un état temporaire auquel nul n'est tenu de se maintenir, sauf convention ou disposition légale contraire. Le partage se divise en deux catégories : le partage par consentement mutuel, qui intervient par accord de tous les associés, et le partage judiciaire, prononcé par les tribunaux en cas d'impossibilité d'accord. Le partage est soumis à plusieurs conditions et dispositions, dont les plus importantes sont la capacité juridique des associés, la divisibilité du bien sans préjudice significatif et la nature du bien détenu en commun (bien immobilier ou mobilier). Le partage peut également être entravé par certains obstacles, tels qu'un accord temporaire de maintien de la propriété commune ou la constitution de droits de tiers sur le bien. Le partage entraîne des conséquences juridiques importantes, notamment la dissolution de la propriété commune et la transformation de la part de chaque associé en un droit de propriété distinct. Les associés bénéficient d'une protection juridique contre les réclamations et les litiges, conformément à la loi. Le partage est déclaratif de droits, et non constitutif. Un associé est considéré comme propriétaire de sa part dès la constitution de la propriété commune, et non à compter de la date du partage. L'étude des dispositions régissant le partage des biens détenus en commun revêt une importance particulière, car elle met en lumière leur rôle dans la garantie de la stabilité juridique et la protection des droits des associés, ainsi que leur contribution à la réduction des litiges pouvant découler du maintien de la propriété commune.
Keywords: Keywords: Jointly، Owned Property; Effects; Separation; Appeal; -الكلمات المفتاحية. القسمة- المال الشائع - الآثار- الافراز- الطعن.; Mots-clés : Partage; Propriété en copropriété; Effets; Séparation; Appel